DISCOURSE ANALYSIS OF ENGLISH LANGUAGE NEWS MEDIA COVERING IN COVID 19 (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In recent months, COVID-19 has caused unprecedented global disruption, affecting every aspect of daily life. In response, news outlets across the world have covered the pandemic in an effort to keep the public informed about the latest developments. While news media has been a crucial source of information during the pandemic, it has also played a critical role in shaping public perception and understanding of the pandemic. Discourse analysis is a valuable tool for investigating the ways in which language is used in news media coverage and how it shapes public opinion. In this essay, we will conduct a discourse analysis of English language news media covering COVID-19. We will examine the language used by news outlets to report on the pandemic, and how that language influences the way the public perceives the virus and the response to it. By analyzing the use of language in news media, this essay aims to contribute to our understanding of how the media shapes public perception of the pandemic and to provide insights into how language can be used to promote effective communication and public awareness during a crisis.